Find Three Ordered Pair Solutions x-y/7=-1

Math
x-y7=-1
Solve the equation for y.
Tap for more steps…
Subtract x from both sides of the equation.
-y7=-1-x
Multiply both sides of the equation by -7.
-7⋅(-y7)=-7⋅(-1-x)
Simplify both sides of the equation.
Tap for more steps…
Simplify -7⋅(-y7).
Tap for more steps…
Cancel the common factor of 7.
Tap for more steps…
Move the leading negative in -y7 into the numerator.
-7⋅-y7=-7⋅(-1-x)
Factor 7 out of -7.
7(-1)⋅-y7=-7⋅(-1-x)
Cancel the common factor.
7⋅-1⋅-y7=-7⋅(-1-x)
Rewrite the expression.
-1⋅(-y)=-7⋅(-1-x)
-1⋅(-y)=-7⋅(-1-x)
Multiply.
Tap for more steps…
Multiply -1 by -1.
1⋅y=-7⋅(-1-x)
Multiply y by 1.
y=-7⋅(-1-x)
y=-7⋅(-1-x)
y=-7⋅(-1-x)
Simplify -7⋅(-1-x).
Tap for more steps…
Apply the distributive property.
y=-7⋅-1-7(-x)
Multiply.
Tap for more steps…
Multiply -7 by -1.
y=7-7(-x)
Multiply -1 by -7.
y=7+7x
y=7+7x
y=7+7x
y=7+7x
Reorder 7 and 7x.
y=7x+7
y=7x+7
Choose any value for x that is in the domain to plug into the equation.
Choose 0 to substitute in for x to find the ordered pair.
Tap for more steps…
Remove parentheses.
y=7(0)+7
Simplify 7(0)+7.
Tap for more steps…
Multiply 7 by 0.
y=0+7
Add 0 and 7.
y=7
y=7
Use the x and y values to form the ordered pair.
(0,7)
(0,7)
Choose 1 to substitute in for x to find the ordered pair.
Tap for more steps…
Remove parentheses.
y=7(1)+7
Simplify 7(1)+7.
Tap for more steps…
Multiply 7 by 1.
y=7+7
Add 7 and 7.
y=14
y=14
Use the x and y values to form the ordered pair.
(1,14)
(1,14)
Choose 2 to substitute in for x to find the ordered pair.
Tap for more steps…
Remove parentheses.
y=7(2)+7
Simplify 7(2)+7.
Tap for more steps…
Multiply 7 by 2.
y=14+7
Add 14 and 7.
y=21
y=21
Use the x and y values to form the ordered pair.
(2,21)
(2,21)
These are three possible solutions to the equation.
(0,7),(1,14),(2,21)
Find Three Ordered Pair Solutions x-y/7=-1

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top